Challenges and Opportunities in Application of Cochlear Implantation - Guevara, Nicolas (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Restoring the hearing and enabling the integration of individuals with severe to profound deafness into mainstream society are remarkable achievements, and this Special Issue contributes to the discussion on the latest challenges and advancements in cochlear implantation. This reprint celebrates the remarkable progress in the field as it is dedicated to showcasing a collection of articles that capture the essence of these developments. These articles collectively provide an insightful overview of the advancements in the field of cochlear implants and cover a wide range of topics, from surgical techniques and electrophysiology to auditory rehabilitation and prognosis factors. Readers and researchers can explore these publications to gain a deeper understanding of the latest developments in this transformative technology with the ultimate goal of improving the lives of cochlear implant recipients.